Efek Nefroprotektif Ekstrak Etanol Bawang Putih (Allium sativum L.) pada Tikus yang Diinduksi Gentamisin - Sujono, Tanti Azizah; Rizki, Fanny Atika (Universitas Muhammadiyah Surakarta)
Gentamicin can induce damage to the kidney because of the accumulation of epithelial cells in the cortex. This accumulation can cause an increase in Reactive Oxygen Species (ROS), which in turn can trigger an increase in free radicals which causes a decrease in kidney function, which can be seen with Blood Urea Nitrogen (BUN) and sCr (serum creatinine) parameters. Garlic (Allium sativum L.) contains several bioactive compounds, including alliin, allisin, ajoene, and allil cysteine. The content of allisin has activity as an antioxidant. This study used a nephrotoxic mouse modelling method with 100 mg/kgBW of gentamicin induction intraperitoneally, then BUN and sCr levels were checked 24 hours after the 10th day induction. This study aimed to determine the effect of garlic ethanol extract in preventing the decline of renal function in rats induced by gentamicin with a parameter of BUN and sCr. The animal test were divided into 5 treatment groups, normal control group, negative controls, and three treatment groups at a dose of 50, 120, and 300 mg/kgBW for 10 days of concurrent treatment between extracts with gentamicin. The results of the study showed that garlic ethanol extract with a dose ofÂ 50, 120, 300 mg/kgBW was able to prevent a decreaseÂ in kidney function due to the administration of gentamicin significantly when compared with negative controls (p 0,05).